Combined effect of glyphosate, saccharin and sodium benzoate on the gut microbiota of rats - M. V. Bilan; M. A. Lieshchova; N. M. Tishkina; V. V. Brygadyrenko (Regulatory Mechanisms in Biosystems, 2019)
Glyphosate is the main component of many broadly used herbicides due to its safety for humans and animals. It is known that the remains of glyphosate are present in allowable doses in fodders and food products, and, consumrd in low doses, it is found in insignificant amounts in milk, eggs and even in the internal organs (liver, kidneys) of animals. For determining combined impact of glyphosate and the commonest food additives on the composition of microbiota of animals, four groups of laboratory male rats were formed, which during 42 days consumed pure water without any restrictions; 1% aqueous solution of glyphosate; 1% solution of glyphosate in combination with 1% solution of sodium benzoate; 1% solution of glyphosate with 1% solution of saccharin. After killing the animals, 1 g of feces were collected and by serial dilutions with 10–1 to 10–9 sterile physiologic solution, a microbiological analysis was undertaken. Out of each dilution an inoculation of the studied material to the elective growth media was performed, by 0.1 cm3, then the material was incubated in a thermostat (24–72 hours, temperature 37 °С), the results were recorded after 24–72 h. The microorganisms were identified by studying morphological parameters, tinctorial, cultural and enzymic properties. Results are provided in CFU/g (colony-forming unit per gramm) of feces. The impact of glyphosate and glyphosate with food additives led to no changes in the number of Escherichia coli and emergence of this species of microorganism with changed enzymic activity. Also no changes occurred in the number of microorganisms of Bifidobactrium and Lactobacillus spp. Addition of glyphosate, and also glyphosate in combination with saccharin to the diet contributes to broader reproduction of microorganisms of Klebsiella, Citrobacter, Enterobacter and Pseudomonas genera. Mixtures of glyphosate and food additives allow conditionally pathogenic yeast-like Candida fungi (Candida glabrata and C. albicans) to spread more widely in the intestine. Significant fluctuations in the number of Enterococcus spp. bacteria genus were observed: by 80 times within range of each of the three experimental groups of rats with addition of herbicide with benzoate and saccharin to the diet.